PENGARUH KOMBINASI DIAPHRAGMATIC BREATHING EXERCISE DAN GUIDED IMAGERY TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RUANG INTERNA I RSUD DR. R. SOEDARSONO KOTA PASURUAN - Sita Hendrakusuma Samsu; budiono budiono; mustayah mustayah (Poltekkes Kemenkes Malang, 2019)
Hypertension is a disease of the cardiovascular system characterized by abnormal blood pressure above 140-90 mmHg. Efforts to reduce blood pressure can be done with non-pharmacological and pharmacological therapy. One of non-pharmacological therapy is a combination of diaphragmatic breathing exercise and guided imagery. The aim of this research was to study a combination of diaphragmatic breathing exercise and guided imagery of changes in blood pressure in hypertensive patients. The research design used is Quasy Experimental with the type of Pre-Post test Control Group Design. The large sample taken was 28 respondents with purposive sampling technique. This study uses the Shapiro-Wilk normality test which shows p-value less than 0.05 so that data distribution is not normal. Furthermore, the analysis of differences using Wilcoxon showed a decrease in blood pressure in the experiment and control group. Although the Mann-Whitney test did not show differences between the experiment and control group, clinically there was a combination of diaphragmatic breathing exercise and guided imagery to decrease blood pressure, as evidenced by the p-value of systolic 0.001 less than p-value diastolic which is 0.007. The combination of diaphragmatic breathing exercise and guided imagery is expected to be an alternative therapy for lowering blood pressure in hypertension. Keywords: Diaphragmatic Breathing Exercise and Guided Imagery, Hypertension